Analisa Peran UMKM Terhadap Perkembangan Ekonomi di Indonesia - Yulya Ammi Hapsari; Putri Apriyanti; Aldi Hermiyanto; Fahrur Rozi (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
Small and Medium Enterprises (SMEs) are productive businesses owned by individuals or single business entities and qualify as micro-enterprises. SMEs are businesses that operate independently and have no direct or indirect links to medium or large-scale companies. This study aims to determine the role of SMEs in participating in building the Indonesian economy. The research method used is the Literature review research method which is carried out by searching, collecting, and analyzing data sources from various previously published scientific works. From the results of this study, SMEs in Indonesia play a very important role in the economy, functioning as job providers, supporters of local products, and significant contributors to GDP. As well as being a supporter of the stability of the Indonesian economy. SMEs also experienced development from 2020 - 2023. Where when Indonesia experienced the Covid-19 pandemic, the economy that occurred this year decreased drastically so that several SMEs suffered losses. But in 2021 the Indonesian economy began to experience a slow increase.